Anti-Incineration Mobilization on WeChat: Evidence from 12 WeChat Subscription Accounts. Issue 8 (17th November 2021) - Zhang, Xixi
ABSTRACT: The role of social media as a mobilization tool has been widely discussed in the digital age, yet empirical evidence on the online consensus mobilization around environmental issues in a relatively restrictive political setting remains largely unexplored. In this study, my aim is to understand how activists strategically harness social media to take collective initiatives and to stimulate communal awareness against current waste disposal industry and waste management policies in China. Using a content analysis method, I examined 557 posts from 12 anti-incineration WeChat subscription accounts with the help of NVivo software. In reference to social constructionism and social movement theories, I argue that consensus mobilization includes three core undertakings: identification, demonstration, and resolution. Investigating the anti-incineration discourse production on WeChat contributes to a more nuanced comprehension of online mobilization in an authoritarian context. And the results have practical implications for environmental-related activism via social media.